Product Development for Lifetime Prolongation via Benchmarking - Serbet, Turgay; Yasar, Mahir; Karayol, Tezel; Akdogan, Anil; Vanli, Ali Serdar (SPRINGER-VERLAG SINGAPORE PTE LTD, 2022)
Companies apply various methods to maintain or increase their market shares in increasing world competition conditions. Benchmarking is one of the best quality improvement tools among these methods especially in automotive industry. Benchmarking presents a continuous process for measuring systems, processes, and products within the organization, and a comparison with the organization performing best practice. This scientific method, which is used to improve the positive aspects of competitors and our own business, finds widespread use. This study examines the product design and improvement project of a local industrial lock mass manufacturer for automotive industry. Since quality management system standards in automotive industry requires continuous quality improvement, these studies are the use of correct methods in the collection and processing of quality data is a big deal. The results achieved here have provided considerable benefit in achieving equivalent quality characteristics with equivalent products. This paper also represents the product development stages in order to improve the quality characteristics of a product. Design and mass manufacturing processes are expressed and reconsideration of the quality characteristics of the product by the collected data via benchmarking is analyzed in detail.
Keywords: Mass production; Quality assurance; Product lifetime; Benchmarking; Position control; Computer Science; Engineering